2015
DOI: 10.1021/acs.iecr.5b00211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Promotion with Ru Addition on the Activity and SO2 Resistance of MnOx–TiO2 Adsorbent for Hg0 Removal

Abstract: In order to investigate the promotional effects of ruthenium (Ru) addition on the structure, activity, and SO2 resistance of MnO x –TiO2 mixed-oxide adsorbent for Hg0 removal at lower temperature, the Ru modified MnO x –TiO2 (RMT) adsorbent, MnO x –TiO2 (MT), and RuO2–TiO2 (RT) were synthesized by the sol–gel method. The fresh and spent adsorbents were characterized by N2 physisorption, XRD, FTIR, H2-TPR, XPS, TG-DSC, and SO2-TPD. It was found that the addition of Ru oxide not only can increase the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 49 publications
(125 reference statements)
2
32
0
Order By: Relevance
“…The broad peak at approximately 25° corresponds to the tape that supported the samples. For the RuO 2 /Co 3 O 4 NWs, the diffraction peaks for the RuO 2 phase are obscured, possibly owing to the small amount of RuO 2 added to the Co 3 O 4 NWs and/or the good dispersion of Ru oxide in the Co 3 O 4 matrix …”
Section: Resultssupporting
confidence: 93%
“…The broad peak at approximately 25° corresponds to the tape that supported the samples. For the RuO 2 /Co 3 O 4 NWs, the diffraction peaks for the RuO 2 phase are obscured, possibly owing to the small amount of RuO 2 added to the Co 3 O 4 NWs and/or the good dispersion of Ru oxide in the Co 3 O 4 matrix …”
Section: Resultssupporting
confidence: 93%
“…13, the 2%Fe/TiO 2 catalyst exhibited three desorption peaks in the temperature ranges 100 to 300 °C, 350 to 700 °C and 750 to more than 1000 °C, which can be attributed to weakly and physically adsorbed SO 2 , moderately bonded sulfate species and strongly bonded sulfate species, respectively 44 . The peak at 228 °C corresponded to the physically adsorbed SO 2 on the catalyst surface, 45,46 the shoulder peak positioned at 653 °C could probably be attributed to the decomposition of sulfated titania (TiO 2 –SO 4 2− ) 47 and the high‐temperature peak located at 938 °C was assigned to SO 2 chemically adsorbed in the catalyst bulk 46,48 . However, for the 1.5%Mo–0.5%Fe/TiO 2 catalyst, only two desorption peaks were observed.…”
Section: Resultsmentioning
confidence: 97%
“…The peaks at around 220 °C were ascribed to the physical absorption of SO 2 molecules on the surface of the catalysts. The peaks at 560 and 598 °C were ascribed to the formation of CuSO 4 species on the 1% Cu–1% Fe/TiO 2 . , The peaks at 653 and 687 °C were assigned to the strong adsorption between TiO 2 and SO 2 on the catalyst surface. , The above four peaks belonged to the sulfate species with moderate adsorption strength. The peaks at 914 and 938 °C were attributed to the strongly bound sulfates with the interior of the catalyst cell, , which could destroy the structure of the catalyst.…”
Section: Resultsmentioning
confidence: 98%
“…TiO 2 possessed the advantages of large specific surface area, excellent chemical stability, and abundant reserves and was regarded as a promising catalyst for simultaneous removal of NO x and SO 2 . Recent studies have shown that the introduction of Fe on the TiO 2 could significantly enhance the catalytic activity in the decomposition of H 2 O 2 for simultaneous removal of NO x and SO 2 . , However, the excellent NO x removal efficiency was obtained with large consumption of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%